THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE SOCIAL SERVICE OFFICE OF TONDANO MINAHASA DISTRICT - Mandagi, Marthinus; R. Siwij, Devie S.; Y. Malingkas, Helsi (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This research aims to determine the significant influence of the independent variable on the dependent variable. The dependent variable in this research is employee performance, while the independent variable is the work environment. In this research, the method used was a quantitative research method with a sample of 56 people, where the number of samples was taken using a saturated sampling technique, where all members of the population were sampled. The data collection technique used in this research is by distributing questionnaires to respondents, and the questionnaire in this research uses a Likert scale. The results obtained by researchers after carrying out regression analysis, namely that there is a positive and significant influence of work environment variables on employee performance, which means that if the work environment improves it will also have an impact on increasing employee performance. Penelitian ini bertujuan untuk mengetahui pengaruh yang signifikan dari variabel independen terhadap variabel dependen. Variabel dependen dalam penelitian ini adalah kinerja karyawan, sedangkan variabel independennya adalah lingkungan kerja. Dalam penelitian ini metode yang digunakan adalah metode penelitian kuantitatif dengan sampel sebanyak 56 orang, dimana jumlah sampel diambil dengan menggunakan teknik sampling jenuh, dimana semua anggota populasi dijadikan sampel. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah dengan cara menyebarkan kuesioner atau angket yang disebarkan kepada responden, dan kuesioner dalam penelitian ini menggunakan skala likert. Hasil yang diperoleh peneliti setelah melakukan analisis regresi, yaitu terdapat pengaruh positif dan signifikan variabel lingkungan kerja terhadap kinerja karyawan, yang artinya apabila lingkungan kerja meningkat maka akan berdampak pula pada peningkatan kinerja karyawan.